madie05
contestada

Write an expression (4x-2)*6(2x+7) in the standard form of a quadratic expression, ax^2+bx+c. What are the values of the coefficients of each term and the constant term?

Respuesta :

Answer:

a=48

b=-192

c=84


Step-by-step explanation:

figure it out yourself :3 jk Idrk


Answer:

see explanation

Step-by-step explanation:

given (4x - 2) × 6(2x + 7), then

= 6(4x - 2)(2x + 7) ← expand factors using FOIL

= 6(8x² + 28x - 4x - 14)

= 6(8x² + 24x - 14) ← distribute

= 48x² + 144x - 84 ← in standard form

with a = 48, b= - 144, c = - 84


ACCESS MORE